Comparative Thermophysiology of Marine Synechococcus CRD1 Strains Isolated From Different Thermal Niches in Iron-Depleted Areas - Ferrieux, Mathilde; Dufour, Louison; Doré, Hugo; Ratin, Morgane; Guéneuguès, Audrey; Chasselin, Léo; Marie, Dominique; Rigaut-Jalabert, Fabienne; Le Gall, Florence; Sciandra, Théo; Monier, Garance; Hoebeke, Mark; et al. (Frontiers in Microbiology, 2022)
Marine Synechococcus cyanobacteria are ubiquitous in the ocean, a feature likely related to their extensive genetic diversity. Amongst the major lineages, clades I and IV preferentially thrive in temperate and cold, nutrient-rich waters, whilst clades II and III prefer warm, nitrogen or phosphorus-depleted waters. The existence of such cold (I/IV) and warm (II/III) thermotypes is corroborated by physiological characterization of representative strains. A fifth clade, CRD1, was recently shown to dominate the Synechococcus community in iron-depleted areas of the world ocean and to encompass three distinct ecologically significant taxonomic units (ESTUs CRD1A-C) occupying different thermal niches, suggesting that distinct thermotypes could also occur within this clade. Here, using comparative thermophysiology of strains representative of these three CRD1 ESTUs we show that the CRD1A strain MITS9220 is a warm thermotype, the CRD1B strain BIOS-U3-1 a cold temperate thermotype, and the CRD1C strain BIOS-E4-1 a warm temperate stenotherm. Curiously, the CRD1B thermotype lacks traits and/or genomic features typical of cold thermotypes. In contrast, we found specific physiological traits of the CRD1 strains compared to their clade I, II, III, and IV counterparts, including a lower growth rate and photosystem II maximal quantum yield at most temperatures and a higher turnover rate of the D1 protein. Together, our data suggests that the CRD1 clade prioritizes adaptation to low-iron conditions over temperature adaptation, even though the occurrence of several CRD1 thermotypes likely explains why the CRD1 clade as a whole occupies most iron-limited waters.